Kerajinan Gerabah Di Desa Jati Kec. Jaten Kab. Karanganyar - Sunarmi Sunarmi (Ornamen, 2004)
This writing gave emphazises on the problems about (1) Why the Banaran’s society in Jati village has still been preserved work as gerabah maker, (2) How ia asan the making process is, (3) flow about the gerabah products in the village. This research used anthropological strategy with ethnographical approach. The data collection technique were the involued observation and deeply interview. The data validity has been done by: (1) triangulation of data sources, (2) peer debriefing, (3) data rechecking. The technique of analysis by interactive model. The observation results showed: (1) Given the activities of the society in Jati village as gerabah maker are induced by pressence of two motivations, that 3ndun ~ are, main motivations in form of: economical demand, hereditary belief that they would get enough wealth from this activity; the belief that there is little campetitor; and the supported motivations: this skill obtained hereditarily, free materials are available and there are consumers. (2) The process in making Jakarta gerabah Is conducted traditionally. (3) The kinds of products are kendhit (cooking pots) to boil medicinal herbs and placenta pots, the average number could obtained is WX)-120 products per five days. The products are marketed to the potition clinics and the boiled medicinal herb stores. society in Jati village has still been preserved work as gerabah maker, (2) How ia asan    the making process is, (3) flow about the gerabah products in the village. This research used anthropological strategy with ethnographical approach. The data collection technique were the involued observation and deeply interview. The data validity has been done by: (1) triangulation of data sources, (2) peer debriefing, (3) data rechecking. The technique of analysis by interactive model. The observation results showed: (1) Given the activities of the society in Jati village as gerabah maker are induced by pressence of two motivations, that are, main motivations in form of: economical demand, hereditary belief that they would get enough wealth from this activity; the belief that there is little campetitor; and the supported motivations: this skill obtained hereditarily, free materials are available and there are consumers. (2) The process in making Jakarta~ ~ gerabah Is conducted traditionally. (3) The kinds of products are kendhit (cook-  inq pots) to boil medicinal herbs and placenta pots, the average number couldobtained is WX)-120 products per five days. The products are marketed to thetion clinics and the boiled medicinal herb stores.